2005
DOI: 10.1074/jbc.m504468200
|View full text |Cite
|
Sign up to set email alerts
|

The Non-catalytic Chitin-binding Protein CBP21 from Serratia marcescens Is Essential for Chitin Degradation

Abstract: The Gram-negative soil bacterium Serratia marcescens uses three different family 18 chitinases to degrade chitin, an abundant insoluble carbohydrate polymer composed of ␤(1,4)-linked units of N-acetylglucosamine. We show that efficient chitin degradation additionally depends on the action of a small noncatalytic protein, CBP21, which binds to the insoluble crystalline substrate, leading to structural changes in the substrate and increased substrate accessibility. CBP21 strongly promoted hydrolysis of crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
348
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 349 publications
(367 citation statements)
references
References 48 publications
13
348
2
4
Order By: Relevance
“…CHI3L1 has no chitinase activity, 3 but still possesses a binding ability to chitin and chitooligosaccharides with high affinity through a preserved hydrophobic substrate binding cleft, 19,16 and the majority of chitinase-producing pathogenic bacteria have the ability to produce chitin-binding molecules such as CBP21. 22 We found that CBP21 knockout strain of S. marcescens significantly reduced in the adhesion but not invasion rate to CECs. Therefore, CBP21 seems to be involved in the bacterial adhesion to CECs, and CHI3L1 may bind to bacteria through CBPs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…CHI3L1 has no chitinase activity, 3 but still possesses a binding ability to chitin and chitooligosaccharides with high affinity through a preserved hydrophobic substrate binding cleft, 19,16 and the majority of chitinase-producing pathogenic bacteria have the ability to produce chitin-binding molecules such as CBP21. 22 We found that CBP21 knockout strain of S. marcescens significantly reduced in the adhesion but not invasion rate to CECs. Therefore, CBP21 seems to be involved in the bacterial adhesion to CECs, and CHI3L1 may bind to bacteria through CBPs.…”
Section: Discussionmentioning
confidence: 71%
“…21 More importantly, the majority of chitinaseproducing pathogenic microorganisms contain a gene encoding for the homolog of the cbp21 gene, suggesting the presence of a potential binding ability of chitinase-producing pathogenic bacteria to chitin via CBP21 homolog. 22 In this study, we propose a new possibility that CHI3L1 expressed on CECs binds to bacterial CBP21 homolog via chitin or chitin-like molecule, and this binding subsequently enhances the adhesion of these bacteria to CECs. To identify the exact mechanism of how CHI3L1 enhances the bacterial adhesion on CECs in vitro, we utilize S. marcescens wild type (WT) in its mutant form and CBP21-overexpressing nonpathogenic E. coli.…”
mentioning
confidence: 94%
“…Thus, CBM33, which is highly expressed in chitin-degrading bacteria such as Serratia marcescens, potentiates the chitinases from this organism, particularly during the latter stages of the degradative process when the glycoside hydrolases are attacking highly crystalline forms of the polysaccharide (Vaaje-Kolstad et al, 2005a). More modest potentiation of cellulases by "noncatalytic" bacterial CBMs has also been reported (Moser et al, 2008), while it has been suggested that several noncatalytic fungal proteins may play a role in plant cell wall disruption.…”
Section: How Do Cbms Potentiate Catalysis?mentioning
confidence: 96%
“…8,9) and most importantly, these proteins act synergistically with chitinases. 10,11 In a very recent study, it was shown that these proteins in fact are enzymes that cleave chitin chains while still being in their crystalline context, using an unprecedented mechanism that involves a hydrolytic and an oxidative step. 12 Thus, the CBM33 generates two new chain ends on the crystalline surface, one normal nonreducing and an ''oxidized reducing end,'' that is, an aldonic acid.…”
Section: Introductionmentioning
confidence: 99%